Bisensitive Hydrogel with Volume Compensation Properties for Force Compensation Sensors - Binder, Simon; Krause, Andreas Torsten; Voit, Brigitte; Gerlach, Gerald (IEEE Sensors Letters, 2017)
Hydrogel-based sensors using the force compensation method show a strongly decreased dynamic drift and a much shorter response time. The sensor setup using a piezoresistive pressure sensor to measure and control the pressure equilibrium becomes complex since an external force, e.g., caused by compressed air or a second hydrogel, must be applied from the opposite side. In addition, the swelling pressure of the hydrogel can lead to internal damage of the polymer chains when exposed to high force impacts. A particularly tailored bisensitive hydrogel was designed and synthesized to address these problems. It simultaneously fulfills the functions of a transducer (for sensing) and of an actuator (for volume compensation). The force compensation thus occurs internally within one single hydrogel, and an external force is no longer required. In the particular case considered in this article, the hydrogel was designed to be sensitive to salt concentration cNaCl and to temperature v. As a result, it was possible to quasi-statically maintain the volume at a constant value for different values of cNaCl by applying a corresponding temperature v.
CRIS-Team Scopus Importer:2023-03-20
Keywords: bisensitive hydrogels; Chemical and biological sensors; chemical transducers; force compensation; hydrogel-based sensors